Barriers to Strategic Execution of Small and Medium Sized Enterprises in Quang Nam Province Construction Industry - Hai, Hoang Van; Quang, Doan Ngoc; Trung, Le Thanh (VNU JOURNAL OF ECONOMICS AND BUSINESS, 2018)
Nowadays, strategic governance is considered indispensible for any enterprise. Moreover, it is globalization and economic integration that have led to fierce competition among enterprises; therefore the enterprises must have an appropriate strategy. In strategic governance, implementation of a strategy plays a key role. This step even has a decisive part for small and medium sized enterprises (SMEs) because they often have fewer advantages in the nowadays fiercely competitive market. In this paper, the obstacles in implementing a strategy in SMEs working in the construction field in Quang Nam province are studied in order to examine relevant theoretical issues and to figure out challenges. Also some solutions are proposed to help the SMEs successfully conduct their strategies.